High-wear-resistance double-sheath automobile high-voltage cable
By adopting a high-wear resistant double-layer sheath structure in high-voltage cables, combined with specific process and material combinations, the shortcomings in existing high-voltage cables in terms of mechanical properties, chemical stability and electrical properties are solved, and the overall performance of the cable is significantly improved, and it is suitable for high-voltage wiring harness applications in new energy vehicles.
Patent Information
- Application Number
- CN202411750492.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
Existing high-voltage cables have shortcomings in mechanical properties, chemical stability and electrical properties, especially in complex environments in the vehicle, the protective layer design is not fine enough, and the conductor performance optimization is insufficient.
It adopts a high wear-resistant double-layer sheath structure, including an inner insulation layer, a tinned copper wire braided shielding layer, a ceramicized fire-resistant material layer and a halogen-free, low smoke-free, flame-retardant, irradiated crosslinked polyolefin outer sheath. Through a specific process and material combination, the mechanical strength, chemical stability and electrical properties of the cable are enhanced.
It significantly improves the wear resistance, tear resistance, chemical stability and electromagnetic shielding performance of the cable, enhances the stability and safety of the cable in high-voltage and high-temperature environments, and is suitable for high-voltage wiring harness applications in new energy vehicles.
Smart Images

Figure CN119811760A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile high-voltage cables, in particular to a highly wear-resistant double-layer sheathed automobile high-voltage cable. Background Art
[0002] The new energy vehicle market is booming, and the demand for high-voltage connection cables for in-vehicle batteries has increased accordingly. Copper core high-voltage cables have certain advantages, but silicone insulated high-voltage cables have many limitations. In terms of mechanical properties, silicone has poor wear resistance and tear resistance, and is easily damaged in the complex environment inside the car, affecting the reliability of the cable. In terms of chemical stability, silicone is not oil-resistant, and its performance decreases after contact with oil. The electrical performance is unstable under extreme conditions, and the resistivity is easy to change. In terms of thermal performance, the heat dissipation is poor when the vehicle is running, which accelerates the aging of the insulation layer. These problems restrict its application. In the context of the increasing degree of automotive electronics and the increase in the application of high-voltage systems, it is urgently needed to improve it. Therefore, the research and development of highly wear-resistant double-layer sheathed automotive high-voltage cables has become inevitable, so as to solve the above problems and meet the development needs of the automotive industry.
[0003] Chinese patent announcement number CN207977132U2 discloses a high-voltage cable for new energy vehicles, comprising a copper conductor, a cross-linked polyolefin insulation layer, a tinned braided shielding layer, an aluminum-plastic composite tape shielding layer and a cross-linked polyolefin outer sheath, wherein the copper conductor, the cross-linked polyolefin insulation layer, the tinned braided shielding layer, the aluminum-plastic composite tape shielding layer and the cross-linked polyolefin outer sheath are arranged in sequence from the inside to the outside of the cable; the coordinated design of this structure and material enables the voltage level of the high-voltage cable to be divided into 600V, 1000V and 1500V, and the maximum allowable temperature for long-term operation is 125°C. The cable is mainly used for high-voltage cables in new energy vehicles, has excellent comprehensive properties such as high voltage resistance, oil resistance and wear resistance, and can meet market demand;
[0004] However, the structure of the above method is relatively simple, the protective layer design is not sophisticated enough, the fire protection design is single, and it is lacking in the optimization of conductor performance. Summary of the invention
[0005] The main purpose of the present invention is to provide a highly wear-resistant double-layer sheathed automotive high-voltage cable, which can effectively solve the problems of relatively simple structure, insufficiently refined protective layer design and lack of conductor performance optimization.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A highly wear-resistant double-layer sheathed automotive high-voltage cable comprises the following steps:
[0008] S1. Conductor preparation: Oxygen-free copper wire is selected for twisting to form a conductor with a specific twisted structure;
[0009] S2, inner insulation layer coating: Thermosetting silicone rubber material is used as the inner insulation layer material, and it is coated on the conductor surface through extrusion process;
[0010] S3. Shielding layer setting: a tinned copper wire braided shielding layer and an aluminum foil wrapped shielding layer are sequentially set outside the inner insulating layer;
[0011] S4, inner sheath and middle layer construction: special silicone rubber with antioxidant added is used as the inner sheath material, and the inner sheath is formed by extrusion process, and then a polyether polyurethane elastomer buffer layer and a carbon fiber braided stress absorption layer are added to the outside of the inner sheath in sequence;
[0012] S5. Adding a fireproof layer: adding a layer of ceramic fireproof material outside the stress absorption layer;
[0013] S6. Cross-linking of outer sheath: 150℃ halogen-free, low-smoke, flame-retardant radiation-cross-linked polyolefin is used as the outer sheath material, which is coated on the outside of the fireproof layer through the radiation cross-linking process. The thickness of the outer sheath is 1.5-2.5mm;
[0014] S7. Performance test: The prepared cables are subjected to abrasion resistance test for 10,000 times in sequence, and then subjected to a withstand voltage test of AC1 kV for 30 minutes, and then the voltage is increased to AC5kV for 5 minutes for a withstand voltage test.
[0015] Preferably, the conductor in step S1 is composed of 7 strands of oxygen-free copper wires, each strand of the oxygen-free copper wire has a diameter of 0.3 mm, a twisting pitch of 15 mm, and a layered twisting structure, with adjacent layers twisted in opposite directions.
[0016] Preferably, the hardness of the thermosetting silicone rubber material in step S2 is 50 Shore A, the thickness of the inner insulating layer is 1.0 mm, and the temperature of the extrusion process is 170-180°C.
[0017] Preferably, the diameter of the tinned copper wire of the tinned copper wire braided shielding layer in the step S3 is 0.12 mm, the braiding angle is 45 degrees, and the thickness of the aluminum foil of the aluminum foil wrapped shielding layer is 0.1 mm.
[0018] Preferably, the tear strength of the special silicone rubber in step S4 is 13-15 kN / m, the thickness of the inner sheath is 1.4 mm, the pressure of the extrusion process is 3 MPa, the thickness of the polyether polyurethane elastomer buffer layer is 0.35 mm, the hardness is 85 Shore A, the thickness of the carbon fiber braided stress absorption layer is 0.45 mm, and the diameter of the carbon fiber monofilament is 6 μm.
[0019] Preferably, the thickness of the ceramicized fireproof material layer in step S5 is 0.5 mm, and the ceramicization temperature is 850-950°C.
[0020] Preferably, the oxygen index of the halogen-free low-smoke flame-retardant radiation cross-linked polyolefin material in step S6 is in the range of 33% to 36%, the cross-linking degree is in the range of 72% to 78%, the outer sheath thickness is 2.0 mm, and the radiation cross-linking dose is 10 kGy.
[0021] Preferably, the scraping force of the scratch resistance test in step S7 is 10N, the scraping speed is 30mm / s, the insulation resistance of the cable after the test is 1.5×1012Ω, and the partial discharge of the cable in the withstand voltage test is 2pC.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention has excellent performance. It adopts a double-layer sheath structure. The cross-linked polyolefin outer layer enhances wear resistance and tear resistance, effectively copes with friction and external forces in the complex environment inside the car, and improves chemical corrosion resistance and water resistance, so that it can resist the invasion of chemicals and moisture. In terms of temperature adaptability, it combines the advantages of silicone and cross-linked polyolefin, improves heat resistance and slows down thermal aging, has good flame retardant properties, reduces fire risks, improves insulation performance, improves electromagnetic shielding effect, ensures signal transmission, has strong stability in the high-voltage environment of the car, and has been tested for pressure resistance and wear resistance, and is highly suitable for new energy vehicles.
[0024] 2. In terms of market promotion, with the vigorous development of the new energy vehicle industry, the demand for the present invention as a key material for high-voltage wiring harnesses has increased with the growth of sales. The increasing electrification of traditional fuel vehicles and the application of high-voltage systems have also expanded its market space. In terms of policy, the new energy vehicle industry policy and environmental protection policy have given strong support. The improvement of industry standards has ensured product quality, raised the market entry threshold, and promoted the survival of the fittest among enterprises. Technological innovation has not only improved performance, but also reduced costs and enhanced market competitiveness. Its unique design and performance advantages have given it broad prospects in the automotive field and will help promote the development of the industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the overall structure diagram of the present invention;
[0026] Figure 2 It is a cross-sectional view of the present invention.
[0027] In the figure: a, conductor; b, inner insulation layer; c, tinned copper wire braided shielding layer; d, aluminum foil wrapped shielding layer; e, inner sheath; f, buffer layer; g, stress absorption layer; h, fireproof layer; i, outer sheath. DETAILED DESCRIPTION
[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0029] A highly wear-resistant double-layer sheathed automotive high-voltage cable comprises the following steps:
[0030] S1. Preparation of conductor a: Oxygen-free copper wire is selected for twisting. The purity of the oxygen-free copper wire is not less than 99.99% and the oxygen content is not higher than 0.001%. The wire is drawn into a single wire, and then multiple strands of the single wire are twisted. The bundle twisting is first performed with 3 layers, and the directions of each layer are left, right, and left in sequence. Then, concentric re-twisting is performed with 2 layers, and the directions of the re-twisting are right and left, respectively, to form a conductor a with a specific twisting structure.
[0031] S2. Inner insulation layer b coating: Thermosetting silicone rubber material is used as the material of the inner insulation layer b. The thermosetting silicone rubber material is heated and evenly coated on the surface of the conductor a through an extruder at an extrusion speed of 0.5-1.0m / min. The thickness of the inner insulation layer b is controlled between 0.8-1.2mm. After extrusion, it immediately enters a cooling water tank with a length of 5-10m for cooling and shaping. The cooling water temperature is 20-30℃ and the water flow rate is 0.5-1.0m / s.
[0032] S3. Shielding layer setting: Tinned copper wire braided shielding layer c and aluminum foil wrapped shielding layer d are sequentially arranged outside the inner insulating layer b. After the tinned copper wire braided shielding layer c is woven, it is slightly calendered. The roller temperature of the calendering equipment is 50-70°C. The aluminum foil is wrapped around the shielding layer d. During the wrapping process, the aluminum foil should be flat and tightly attached to the outside of the tinned copper wire braided shielding layer c. The wrapping speed is 5-10m / min. After the wrapping is completed, it is rolled up. The winding tension is controlled at 5-10N. The outer diameter deviation of the aluminum foil wrapped shielding layer d after rolling is within ±0.5mm;
[0033] S4, inner sheath e and middle layer construction: special silicone rubber with antioxidant added is used as the material of inner sheath e, and it is extruded by an extruder in the temperature range of 150-170℃ to form inner sheath e. The pressure during extrusion is maintained at 2.5-3.5MPa. After extrusion, the surface is smoothed. The roundness deviation of the treated inner sheath e is within ±0.3mm. Then, a layer of polyether polyurethane elastomer buffer layer f and a layer of carbon fiber braided stress absorption layer g are added to the outside of the inner sheath e in sequence. The buffer layer f material is heated to 80-100℃, and it is bonded to the outside of the inner sheath e through a bonding process. During the bonding process, it is ensured that there are no bubbles and wrinkles. After bonding, it is cooled, and the cooling rate is 5-10℃ / min. The peel strength between the cooled buffer layer f and the inner sheath e is not less than 5N / cm. Then, the treated carbon fiber braided stress absorption layer g is wound around the outside of the buffer layer f through a winding process. The tension is kept uniform during the winding process. The axial tensile strength of the stress absorption layer g after winding is not less than 100MPa.
[0034] S5. Adding fireproof layer h: Add a layer of ceramic fireproof material outside the stress absorption layer g, and select ceramic fireproof material with a ceramic temperature of 850-950℃ and a heating line shrinkage rate of not more than 5% (under the condition of 800℃×2h) as the material of the fireproof layer h. Mix the ceramic fireproof material with an appropriate amount of coupling agent. The coupling agent addition amount is 1% to 3% of the mass of the fireproof material. The mixing time is 10-20min, and then it is made into a thin sheet with a thickness of 0.4-0.6mm. It is bonded to the outside of the stress absorption layer g through a bonding process. After bonding, it is cured. The curing temperature is 180-220℃, and the curing time is 2-4h. The shear strength of the cured fireproof layer h and the stress absorption layer g is not less than 8N / mm 2 ;
[0035] S6. Cross-linking of outer sheath i: Use 150℃ grade halogen-free low-smoke flame-retardant radiation cross-linked polyolefin as the outer sheath i material, and dry the outer sheath i material in a vacuum environment for 2-4h at a drying temperature of 60-80℃ to remove moisture and volatiles in the material, heat the outer sheath i material to 140-160℃, and use an extruder to coat it on the outside of the fireproof layer h at an extrusion speed of 0.8-1.2m / min. The irradiation source is an electron accelerator. During the irradiation process, the cable passes through the irradiation area at a uniform speed of 5-10m / min. The oxygen content in the irradiation area is controlled below 0.1% to prevent material oxidation. The irradiation source is an electron accelerator. During the irradiation process, the cable passes through the irradiation area at a uniform speed of 5-10m / min. The oxygen content in the irradiation area is controlled below 0.1% to prevent material oxidation.
[0036] S7. Performance test: Fix the prepared cable on the scratch and abrasion resistance test equipment, use a tungsten carbide scraper with a diameter of 5-8mm, and perform 10,000 scrape and abrasion tests on the cable outer sheath i. During the test, monitor the insulation resistance of the cable in real time. After the test, the insulation resistance of the cable is not less than 1.2×1012Ω. Then connect the cable to the voltage test equipment and perform a voltage test of AC1kV for 30min. During the test, monitor whether there is breakdown. Then increase the voltage to AC5kV for 5min for voltage test. During the test, monitor the partial discharge of the cable. The partial discharge does not exceed 3pC. The voltage measurement accuracy of the voltage test equipment is ±0.5%.
[0037] See also Figure 1 The conductor a in step S1 is composed of 7 strands of oxygen-free copper wires, each strand has a diameter of 0.3 mm, a twisting pitch of 15 mm, and a layered twisting structure, with adjacent layers twisted in opposite directions.
[0038] Furthermore, the above structure can better adapt to bending and vibration in complex automotive wiring, reduce the risk of conductor a damage due to mechanical stress, ensure continuous and stable current transmission, and improve the overall durability and reliability of the cable.
[0039] See also Figure 1 The hardness of the thermosetting silicone rubber material in step S2 is 50ShoreA, the thickness of the inner insulating layer b is 1.0mm, and the temperature of the extrusion process is 170-180℃.
[0040] Furthermore, the above-mentioned material properties and process parameters ensure that the insulating layer fits tightly to the conductor a, effectively preventing current leakage and short circuit. Its good flexibility prevents the insulating layer from cracking due to vehicle vibration and other factors during use, ensuring long-term stable electrical insulation performance and adapting to the stringent requirements of the automotive high-voltage system.
[0041] The connection method between conductor a and inner insulating layer b is as follows: conductor a is formed by twisting multiple strands of oxygen-free copper wires, and the surface of conductor a after twisting has a certain degree of roughness. When coating the inner insulating layer b, the thermosetting silicone rubber material is plasticized at a high temperature of 170-180°C, extruded through an extruder, and uniformly coated on the surface of conductor a at a speed of 0.5-1.0m / min. Since the thermosetting silicone rubber material has good fluidity and adhesion, under the combined effect of extrusion pressure and the surface roughness of conductor a, the silicone rubber can fit closely to conductor a, fill the gap of the twisted conductor a, and form a strong physical bond. At the same time, during the cooling and shaping process, the thermosetting silicone rubber gradually solidifies, further enhancing the bonding strength with conductor a, ensuring that the connection between conductor a and inner insulating layer b is tight and seamless, effectively preventing relative displacement between conductor a and the insulating layer, and ensuring electrical insulation performance.
[0042] See also Figure 1 The diameter of the tinned copper wire of the tinned copper wire braided shielding layer c in step S3 is 0.12 mm, the braiding angle is 45 degrees, and the thickness of the aluminum foil of the aluminum foil wrapped shielding layer d is 0.1 mm.
[0043] Furthermore, the above-mentioned precise parameter settings build a highly efficient electromagnetic shielding system, which can effectively resist external electromagnetic field interference, prevent internal signal radiation, and ensure the accuracy and stability of signal transmission in the automotive electrical system. It has obvious advantages, especially in complex electromagnetic environments, and improves the overall performance of the system.
[0044] The connection method between the inner insulating layer b and the shielding layer is as follows: the surface of the inner insulating layer b is smooth, and the tinned copper wire braided shielding layer c is tightly woven on it, relying on the braiding pressure to form multiple points of contact with the insulating layer to increase the friction, and the aluminum foil wrapped shielding layer d is tightly fitted, and the three together form an electromagnetic shielding as a whole by utilizing their own viscosity and pressure, which effectively isolates the electromagnetic field, ensures the stability of signal transmission, and adapts to the complex electromagnetic environment of the automotive electrical system.
[0045] See also Figure 1 The tear strength of the special silicone rubber in step S4 is 13-15 kN / m, the thickness of the inner sheath e is 4 mm, the pressure of the extrusion process is 3 MPa, the thickness of the polyether polyurethane elastomer buffer layer f is 0.35 mm, the hardness is 85 Shore A, the thickness of the carbon fiber braided stress absorption layer g is 0.45 mm, and the diameter of the carbon fiber monofilament is 6 μm.
[0046] Furthermore, the silicone rubber inner sheath e can provide good protection, the polyether polyurethane elastomer buffer layer f can effectively disperse the external force, and the stress absorption layer g can prevent stress concentration. The three together can enhance the cable's ability to resist mechanical damage, extend its service life, and ensure stable cable performance in a complex mechanical stress environment.
[0047] The connection method between the shielding layer and the inner sheath e is as follows: after the shielding layer is completed, the special silicone rubber inner sheath e is covered by extrusion. The extrusion pressure makes the material fill the gaps in the shielding layer, and the connection is firmly connected by viscosity and friction. The inner sheath e provides protection for the inner layer structure, and cooperates with the shielding layer to enhance the mechanical strength and stability of the cable, ensuring the relative position of each layer structure is stable when subjected to force, maintaining the overall performance of the cable, and meeting the mechanical protection requirements in automotive use;
[0048] The connection method between the inner sheath e and the buffer layer f is as follows: after the surface of the inner sheath e is smoothed, the polyether polyurethane elastomer buffer layer f is laminated thereon at high temperature. During lamination, the material viscosity and pressure are used to ensure close contact without bubbles or wrinkles. After cooling, the peel strength reaches the standard. The buffer layer f absorbs and disperses mechanical stress to protect the inner sheath e. The good connection enables it to work in coordination with the inner sheath e, enhances the cable's ability to resist mechanical damage, and copes with vibration, extrusion, etc. during vehicle operation.
[0049] The buffer layer f and the stress absorption layer g are connected in the following manner: after the buffer layer f is completed, the carbon fiber braided stress absorption layer g impregnated with epoxy resin adhesive and dried and cured is wound on it. During the winding process, the tension is uniform, the epoxy resin makes the two tightly bonded, and the large-area contact enhances the connection firmness. The stress absorption layer g effectively absorbs stress, prevents stress concentration from damaging the cable, and protects the internal structure together with the buffer layer f, prolongs the cable life, and adapts to the dynamic stress environment during vehicle operation.
[0050] See also Figure 1 The thickness of the ceramic fireproof material layer in step S5 is 0.5 mm, and the ceramicization temperature is 850-950°C.
[0051] Furthermore, when high temperature or fire occurs, the fireproof layer h can quickly ceramicize to form a solid barrier to prevent flames and heat from invading, protect the internal structure, maintain the basic functions of the cable, greatly improve the fire safety of the cable, ensure the safety of cars and personnel, and reduce fire hazards.
[0052] The connection method of the stress absorption layer g and the fireproof layer h is as follows: after the stress absorption layer g is wound, the ceramic fireproof material layer mixed with the coupling agent is attached thereto, the lamination pressure and the coupling agent enhance the bonding force, and the curing treatment ensures the shear strength. In case of high temperature or fire, the fireproof layer h is quickly ceramicized to block the heat of the flame, and is closely connected with the stress absorption layer g to ensure the protective effect, maintain the integrity of the internal structure of the cable, improve the fire safety, and ensure the safety of the car and personnel.
[0053] See also Figure 1 The oxygen index of the halogen-free low-smoke flame-retardant radiation cross-linked polyolefin material in step S6 is in the range of 33% to 36%, the cross-linking degree is in the range of 72% to 78%, the thickness of the outer sheath i is 2.0 mm, and the radiation cross-linking dose is 10 kGy.
[0054] Furthermore, the above-mentioned materials and process parameters enable the outer sheath i to have excellent wear resistance, flame retardancy and thermal stability, effectively resist external erosion, maintain stable performance in high temperature and harsh environment, reduce fire risks, meet the use requirements of automotive high-voltage cables, and ensure long-term and reliable operation of the cables.
[0055] The connection method of the fireproof layer h and the outer sheath i is as follows: after the fireproof layer h is bonded and cured, the halogen-free low-smoke flame-retardant radiation-crosslinked polyolefin outer sheath i is extruded and coated, and the extrusion process is tightly bonded, and after radiation crosslinking, it forms a whole with the fireproof layer h. The outer sheath i serves as the last barrier to resist external damage, and is firmly connected with the fireproof layer h to ensure the integrity and stability of the cable structure, jointly protect the internal structure, and ensure the normal operation of the cable in a complex environment, which meets the performance requirements of automobiles for cables.
[0056] See also Figure 1The scraping force of the scratch resistance test in step S7 is 10N, the scraping speed is 30mm / s, and the insulation resistance of the cable after the test is 5×1012Ω; the partial discharge of the cable in the voltage resistance test is 2pC.
[0057] Furthermore, precise test parameters can accurately evaluate the actual performance of the cable, ensuring that it can resist friction, wear and high voltage for a long time under complex automotive operating conditions, ensuring cable quality, improving the reliability and safety of the automotive electrical system, and meeting strict safety standards.
[0058] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A highly wear-resistant double-layer sheathed automotive high-voltage cable, comprising the following steps: S1. Conductor preparation: Oxygen-free copper wire is selected for twisting to form a conductor with a specific twisted structure; S2, inner insulation layer coating: Thermosetting silicone rubber material is used as the inner insulation layer material, and it is coated on the conductor surface through extrusion process; S3. Shielding layer setting: a tinned copper wire braided shielding layer and an aluminum foil wrapped shielding layer are sequentially set outside the inner insulating layer; S4, inner sheath and middle layer construction: special silicone rubber with antioxidant added is used as the inner sheath material, and the inner sheath is formed by extrusion process, and then a polyether polyurethane elastomer buffer layer and a carbon fiber braided stress absorption layer are added to the outside of the inner sheath in sequence; S5. Adding a fireproof layer: adding a layer of ceramic fireproof material outside the stress absorption layer; S6. Cross-linking of outer sheath: 150℃ halogen-free, low-smoke, flame-retardant radiation-cross-linked polyolefin is used as the outer sheath material, which is coated on the outside of the fireproof layer through the radiation cross-linking process. The thickness of the outer sheath is 1.5-2.5mm; S7. Performance test: The prepared cables are subjected to abrasion resistance test for 10,000 times in sequence, and then subjected to a withstand voltage test of AC1 kV for 30 minutes, and then the voltage is increased to AC5kV for 5 minutes for a withstand voltage test.
2. A highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The conductor in step S1 is composed of 7 strands of oxygen-free copper wires, each strand of the oxygen-free copper wire has a diameter of 0.3 mm, a twisting pitch of 15 mm, and a layered twisting structure, with adjacent layers twisted in opposite directions.
3. A highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The hardness of the thermosetting silicone rubber material in step S2 is 50 Shore A, the thickness of the inner insulating layer is 1.0 mm, and the temperature of the extrusion process is 170-180°C.
4. A highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The diameter of the tinned copper wire of the tinned copper wire braided shielding layer in step S3 is 0.12 mm, the braiding angle is 45 degrees, and the thickness of the aluminum foil of the aluminum foil wrapped shielding layer is 0.1 mm.
5. The highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The tear strength of the special silicone rubber in step S4 is 13-15 kN / m, the thickness of the inner sheath is 1.4 mm, the pressure of the extrusion process is 3 MPa, the thickness of the polyether polyurethane elastomer buffer layer is 0.35 mm, the hardness is 85 Shore A, the thickness of the carbon fiber braided stress absorption layer is 0.45 mm, and the diameter of the carbon fiber monofilament is 6 μm.
6. The highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The thickness of the ceramicized fireproof material layer in step S5 is 0.5 mm, and the ceramicization temperature is 850-950°C.
7. The highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The oxygen index of the halogen-free low-smoke flame-retardant radiation cross-linked polyolefin material in step S6 is in the range of 33% to 36%, the cross-linking degree is in the range of 72% to 78%, the outer sheath thickness is 2.0 mm, and the radiation cross-linking dose is 10 kGy.
8. The highly wear-resistant double-layer sheathed automotive high-voltage cable according to claim 1, characterized in that: The scraping force of the scratch resistance test in step S7 is 10N, the scraping speed is 30mm / s, the insulation resistance of the cable after the test is 1.5×1012Ω, and the partial discharge of the cable in the voltage resistance test is 2pC.
Citation Information
Patent Citations
High tension cable for new energy automobile
CN207977132U
Cited By
High-flexibility new energy automobile high-voltage cable and process thereof
CN120565167A